LEARNING STRATEGIES OF STUDENTS HIGH AND LOW ACHIEVEMENT - Mohamad Yunus Laia (Institut Pendidikan Tapanuli Selatan, 2021)
The aim of this research was to know learning strategies applied by seventh semester students of English Language Education Study Program of STKIP Nias Selatan. This research was conducted by using Qualitative research, Case Study Research, to analyze the learning strategies among students of English Language Education study program of STKIP Nias Selatan. The participants of this research were Seventh semester students of English Language Education Study Program which consisted of 46 students. The questionnaire version 7.0 of Strategy Inventory of Language Learning (SILL) and interview were used to collect data of the research. The data were calculated and analyzed manually and classified it into level of learning strategies. The result of this research showed that seventh semester students of English Language Education Study Program of STKIP Nias Selatan applied all of learning strategies, including memory strategies, cognitive strategies, compensation strategies, metacognitive strategies, affective strategies, and social strategies. Most frequent strategies used by students were metacognitive strategies and memory strategies were in the medium level. After conducting this research, the researcher made conclusion that learning strategies that seventh semester students of English Language Education Study Program of STKIP Nias applied have an impact for their achievement. These results are expected to enhance the students’ knowledge to find out what the learning strategies appropriately for themselves and also enhance the teacher or lecturer knowledge about learning strategies that can help them to teach the students especiallyEnglish students.